Estudo do potencial antioxidante, anti-inflamatório e cicatrizante de Bauhinia ungulata L. - Rodrigues, Raphael de Oliveira (2019)
Bauhinia ungulata L. is a species native to Brazil and little is known in respect to its pharmacological properties. Studies carried out with the plant resulted in the isolation and identification of some chemical compounds, among them, flavonoids, bibenzyls, triterpenoids and oxepinic derivatives, for example. The present work aimed to investigate the antioxidant, immunomodulatory, antimicrobial and wound healing activities of Bauhinia ungulata L. on in vitro and in vivo models. A flavonoid-rich fraction was obtained from Bauhinia ungulata L. stem, called ethyl acetate fraction of Bauhinia ungulata (FABU). Total antioxidant capacity of FABU was determined through phosphomolibdenium reduction method. Moreover, to investigate its immunomodulatory activity on cell culture model, LPS-stimulated RAW 264.7 cells were treated with different concentrations of FABU and used to measure the levels of reactive oxygen species (ROS), nitric oxide (NO), hydrogen peroxide (H2O2), as well as thiobarbituric acid reactive substances (TBARS). TNF-α, TGF-β and IL-10 cytokine levels were also measured in culture supernatant. In order to determinate the antimicrobial activity of FABU, antifungal and antibacterial susceptibility testing were performed against Candida albicans, methicillin-sensitive Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa strains. Wound healing assay using A549 human epithelial cells was employed to evaluate the ability of FABU to modulate the cell migration process. In addition, a surgical wound model in C57BL/6 mice was used to study the wound healing potential of FABU, through the analysis of antioxidant parameters, immunomodulators and the rate of wound closure in the early stages of the healing process. FABU did not demonstrate a significant antimicrobial or immunodulatory activities. Nonetheless, a potential antioxidant activity was demonstrated by the phosphomolibdenium reduction assay, as well as, when measured the levels of ROS, NO, H2O2, and TBARS on LPS-stimulated cells. The effects of FABU on the cell migration process demonstrated that the fraction significantly accelerated the reduction of the wound area promoted in the wells containing the cells. In addition, the surgical wound model used to evaluate the beneficial effects of FABU in the initial stages of healing, it was shown that this fraction was effective in significantly reducing the level of lipid peroxidation in the lesions. It was also observed that FABU promoted a significant reduction in the relative gene expression levels of IL-1β and TNF-α in the wound region, contributing significantly to the maintenance of a regulated inflammatory environment. Macroscopic analysis of wound closure checked by photographic follow-up showed that the group treated with the ethyl acetate fraction of Bauhinia ungulata presented a significant reduction in the size of the injured area during evaluated period. The histopathological analysis of the lesions, however, showed no significant difference between the groups tested. In conclusion, the present study demonstrated that FABU presented significant antioxidant activity in vitro and in vivo, capable of contributing to the wound healing process, preventing cellular damage caused by ROS. In addition, treatment with the fraction showed important activity in the cellular migration process through the evaluated model. The data suggest that the ethyl acetate fraction of Bauhinia ungulata L. can interfere in the cascade of cellular damage caused by reactive oxygen and nitrogen species, with promising potential in models of chronic diseases that involve high levels of these molecules.